Equipping future teachers with innovative strategies that increase physical activity in the classroom: a hybrid implementation trial across three Australian universities - Lander, Natalie J.; Mazzoli, Emiliano; Essiet, Inimfon A.; Telford, Amanda; Ridley, Kate; Symington, Naomi; Salmon, Jo (Frontiers in Education, 2023)
TransformEd targets initial teacher education (ITE) to equip future teachers with innovative strategies that increase physical activity in the primary school classroom. This hybrid implementation-effectiveness trial investigated the effects of the TransformEd program when embedded in initial teacher education degrees at two Australian universities (University 1 Single Unit offering; University 2 Dual Unit offering) over a 12-week period, on pre-service teachers’ perceived competence, confidence, and willingness to deliver active pedagogies, in comparison with a third ‘usual practice’ control university. There was a favourable intervention effects on the total teacher perceptions score among pre-service teachers in University 1 compared to the control group pre-service teachers. Further, there was a significant intervention effect on reduced perceived barriers to active strategies in University 1, and a significant increase in perceived effects of active strategies on primary school student outcomes in University 2. Qualitative data suggested the program strengthened the connection between theory and practice (i.e., how pre-service teachers are educated in university and the way they teach in primary schools). The program was motivating to both lecturers and pre-service teachers, resulted in them reflecting on their own teaching practice, and helped with pre-service teacher engagement. Recommendations for improvement included stronger and more explicit alignment with the Australian Professional Standards for Teachers.